Influence of Chain Length of Gradient and Block Copoly(2-oxazoline)s on Self-Assembly and Drug Encapsulation - Sedlacek, Ondrej; Bardoula, Valentin; Vuorimaa-Laukkanen, Elina; Gedda, Lars; Edwards, Katarina; Radulescu, Aurel; Mun, Grigoriy A; Guo, Yong; Zhou, Junnian; Zhang, Hongbo; Nardello-Rataj, Véronique; Filippov, Sergey; et al. (Small (Weinheim an der Bergstrasse, Germany), 2022)
Amphiphilic gradient copolymers represent a promising alternative to extensively used block copolymers due to their facile one-step synthesis by statistical copolymerization of monomers of different reactivity. Herein, an in-depth analysis is provided of micelles based on amphiphilic gradient poly(2-oxazoline)s with different chain lengths to evaluate their potential for micellar drug delivery systems and compare them to the analogous diblock copolymer micelles. Size, morphology, and stability of self-assembled nanoparticles, loading of hydrophobic drug curcumin, as well as cytotoxicities of the prepared nanoformulations are examined using copoly(2-oxazoline)s with varying chain lengths and comonomer ratios. In addition to several interesting differences between the two copolymer architecture classes, such as more compact self-assembled structures with faster exchange dynamics for the gradient copolymers, it is concluded that gradient copolymers provide stable curcumin nanoformulations with comparable drug loadings to block copolymer systems and benefit from more straightforward copolymer synthesis. The study demonstrates the potential of amphiphilic gradient copolymers as a versatile platform for the synthesis of new polymer therapeutics.
Keywords: polymery; kurkumin; Curcumin; hydrofobní a hydrofilní interakce; Micelles; gradient copolymers; Hydrophobic and Hydrophilic Interactions; Polymers; Drug Carriers; self-assembly; micely; poly(2-oxazoline)s; nosiče léků; nanomedicine